Arabic and the case against linearity in historical linguistics - Owens, Jonathan 1951- (Oxford University Press, 2023)
This volume explores nearly 2000 years of the history of the Arabic language, from pre-Islamic Arabic via the Classical era of the Arabic grammarians up to the present day. Jonathan Owens advocates a multiple pathways approach to the development of Arabic, which he shows to be alinear in many respects but multilinear in others
Keywords: Historische Sprachwissenschaft; Sprachentwicklung; Arabisch; Arabic language / History; Historical linguistics; Electronic books